An improved and robust finite element model for simulation of thin-walled steel bolted connections. (1st January 2022) - Ye, Jun; Quan, Guan; Yun, Xiang; Guo, Xi; Chen, Ju
Highlights: A robust finite element model for simulation of thin-walled steel bolted connections proposed. Bolt slippage and bearing mechanism in cold-formed steel connections addressed. Effectiveness of the proposed model is validated against 3 different sets of tests of various structural types. Good agreement between the FE models using the proposed method and available test results. Abstract: Thin-walled cold-formed steel (CFS) structures are widely used in low-storey buildings and are seeing increased applications in multi-storey buildings as well as long-span structures. The bolted connection is one of the most common types of fasteners employed in CFS structures. The bolt slippage and load-bearing mechanism in CFS connections have a significant influence on the structural behaviour of cold-formed steel construction assemblies, which are typically numerically simulated using spring/connector elements. However, the determination of input parameters for the spring/connector elements generally requires load-deformation characteristics obtained from physical tests of lap joints, which are costly and time-consuming. Moreover, the use of spring/connector elements fails to explicitly capture the bolt bearing behaviour, resulting in inaccuracy in the simulation of CFS connections. In this paper, an accurate, efficient and robust numerical method that can fully replicate the behaviour of CFS connections considering both the effects of bolt slippage and bearing has been introduced. In the proposed numerical methodology, the cold-formed plates are modelled using the conventional shell elements, while a number of solid elements are introduced around the bolt holes, enabling the bolt-plate interaction to be explicitly accounted for, with contact pairs defined between the bolts and their surrounding solid element surfaces. The proposed numerical method could find a convergence solution using dynamic implicit solver in the general-purpose finite element (FE) software ABAQUS. Good agreement between the FE models using the proposed method and the available test results of CFS bolted connections were achieved, which sheds light on the promising application of the proposed method for simulating CFS assembled using bolted connections.